Comparison of airway maneuvers (manual in line stabilization, modified jaw thrust, and conventional maneuver) for orotracheal intubation during direct laryngoscopy - Kumari, Santosh; Shashi Kumari; Vandana Singh Delwal; Devi, Vaishno (Asian Journal of Medical Sciences, 2023)
Background: During performing orotracheal intubation with direct laryngoscopy adequate laryngeal visualization depends on proper airway maneuvers. There are different types of airway maneuvers. Aims and Objectives: This study aimed to compare airway maneuvers; manual in line stabilization (MILS), jaw thrust, and conventional maneuver to assess better laryngeal visualization and ease of intubation among them and associated complications. Materials and Methods: This observational study was conducted in 90 adult patients. Patients divided into three groups. Laryngoscopy and intubation in Group M were done in MILS and in group J jaw thrust. In Group C, as conventional maneuver performed. Laryngeal visualization assessed using modified Cormack–Lehane grading and ease of intubation assessed using intubation time, number of attempts between these three groups. The data were compared using ANOVA test, Chi-square test. Results: While comparing between these groups better laryngeal visualization seen in jaw thrust group, while the MILS maneuver worsen the view. Conclusion: The present study concluded that jaw thrust maneuver improved the laryngeal visualization and conventional maneuver made intubation faster and easy.